2005
DOI: 10.1152/ajpheart.01285.2004
|View full text |Cite|
|
Sign up to set email alerts
|

Cardioprotection with palm tocotrienol: antioxidant activity of tocotrienol is linked with its ability to stabilize proteasomes

Abstract: . Cardioprotection with palm tocotrienol: antioxidant activity of tocotrienol is linked with its ability to stabilize proteasomes. Am J Physiol Heart Circ Physiol 289: H361-H367, 2005. First published February 11, 2005 doi:10.1152/ajpheart.01285.2004.-Tocotrienols, isomers of vitamin E, have been found to possess many health benefits. The present study was designed to determine whether tocotrienol has a direct cardioprotective role. Isolated rat hearts were perfused for 15 min with Krebs-Ringer bicarbonate bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 36 publications
2
47
0
Order By: Relevance
“…Some evidence has suggested that T3s have greater potential physiologic functions than TPs (7,8). T3 has been shown to mediate its activity against a variety of chronic diseases, including cardiovascular diseases, neurologic diseases, diabetes, and cancer (9)(10)(11)(12)(13)(14). T3s have shown anticancer activity against cancers such as colon, breast, liver, lung, kidney, prostate, skin, and other cancers both in vitro (15)(16)(17)(18)(19)(20) and in vivo (21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence has suggested that T3s have greater potential physiologic functions than TPs (7,8). T3 has been shown to mediate its activity against a variety of chronic diseases, including cardiovascular diseases, neurologic diseases, diabetes, and cancer (9)(10)(11)(12)(13)(14). T3s have shown anticancer activity against cancers such as colon, breast, liver, lung, kidney, prostate, skin, and other cancers both in vitro (15)(16)(17)(18)(19)(20) and in vivo (21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…We (21) have shown that the proteasome may become dysfunctional as a result of ischemia. TRF was observed to partially protect the proteasome, which may have facilitated the degradation of phospho-c-Src (7).…”
mentioning
confidence: 98%
“…Recently, tocotrienols have been found to be effective in protecting the central nervous system compared with ␣-tocopherol, and tocotrienol inhibited glutamate-induced pp60 c-Src kinase activation in HT4 neuronal cells (27). Tocotrienols have also been found to provide cardioprotection against several cardiovascular diseases (7,(23)(24)(25). A recent study showed that cardioprotection with palm tocotrienols [the tocotrienol-rich fraction (TRF)] was linked with their ability to stabilize proteasomes (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One study indicated that tocotrienol-rich fraction was able to reduce myocardial infarct size, improve postischemic ventricular dysfunction and reduce the incidence of ventricular arrhythmias. Tocotrienol-rich fraction was shown to stabilize 20S and 26S proteosome activities and reduce the ischemia-reperfusioninduced increase in c-Src phosphorylation (Das et al 2005). Esterhuyse et al investigated the effects of red palm oil enriched with tocotrienols and tocopherols on the myocardial nitric oxide-cGMP signaling pathway (Esterhuyse et al 2005).…”
Section: Anti-ischemic Property Of Tocotrienols In Cardioprotectionmentioning
confidence: 99%